Managing Diversity in a Glocalizing World - Selma van Londen; Arie de Ruijter (Fondazione Eni Enrico Mattei (FEEM), 2003)
Our daily lives are governed by products and images originating from all over the world, through the process of globalization. At the same time, however, globalization creates favourable conditions for all forms of particularization, localization and even fragmentation. While individuals and groups acquire mul-tiple identities, the resulting plurality gives rise to conflicts, controversies and variations, but also to attempts to live peacefully together, to co-ordinate activities, and to balance interests. The paper thus suggests (1) a plea for compatibility instead of commonality - with regard to cultural values and (2) a strong emphasis on the interaction model in decision making, i.e. a model which does not advocate uniformity, but the compatibility of views, and in particular, practices. It concerns the coordination and combination of the proper interests of the various actors who have to depend on one another for the satisfaction of their demands or the realization of their objectives.
Keywords: Z10; 330; Managing diversity; globalization; localization; glocalization; compatibility; interaction model